Investigação do planejamento diário no Sistema Last Planner de planejamento e controle da produção em empreendimentos da construção - Souza, Ana Luiza Carvalho de (Universidade Federal de São Carlos, 2021)
Lean construction focuses on generating value for the customer, elimination of waste and enhancement of human potential. Such objectives became of great importance with the growing competitiveness of the construction sector, which boosted the creation of techniques that aim to reduce costs and deadlines. The Last Planner system of planning and control production is a tool developed by Glenn Ballard and Greg Howell looking to reduce uncertainties and workflow variability through collaborative planning based on removing restrictions. Although it has a classic structure with short, medium and long term plans, it is a model of great flexibility and possibility of customization, thereby new practices, that can which aggregate concepts from different methodologies, have been increasingly applied. In this his research project, daily planning was investigated through literature review, conducting interviews with AEC companies that apply the LPS and an exploratory and descriptive case study in a construction project. The objective of the research was to analyze how many and which vertical planning horizons are used in practice, comparing them with the theory already described in the literature. As a result, it was possible to identify the need to update theoretical guidelines to formalize the inclusion of daily planning in the SLP and provide clearer guidelines aiming that companies can consolidate their implementation.
Investigation of daily planning in the Last Planner System of production planning and control in construction projects
Keywords: Sistema Last Planner; Planejamento e controle da produção; Planejamento colaborativo; Planejamento diário; Construção enxuta; Last Planner System; Production planning and control; Collaborative planning; Daily planning; Lean Construction; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL